Learning needs of family physicians, pediatricians and obstetricians to support breastfeeding and inform physician education - Baerg, Krista; Smith-Fehr, Juliet; Marko, Joshua; Loewy, Amanda; Blaser Farrukh, Jill; Olson, Tonia (Canadian Medical Education Journal, 2021)
Background: Physicians require breastfeeding education appropriate to their roles. The aim of this survey was to determine physician learning needs and to inform development of breastfeeding education for physicians. Methods: A cross sectional survey was distributed to family physicians, pediatricians and obstetricians in a tertiary institution. Importance of knowledge to practice and confidence to manage was assessed for 18 learning topics proposed by a multi-specialty physician working group. Descriptive statistics, ANOVA and tests for equality of variances were calculated. Mean values of importance to practice and confidence to manage for each topic suggested learning priorities. Results: The study group included 75 physicians. The most important topics were “informed choice when supporting newborn feeding,” “analgesics, antidepressants and other medications while breastfeeding” and “community resources for breastfeeding support.” Confidence to manage was lowest for “latch assessment,” “what mom can do during pregnancy to promote milk production,” and “risk factors for delayed lactogenesis.” Preferred learning formats were 15-minute online modules and grand rounds. Conclusions: Physicians acknowledged the importance of all topics but report lowest confidence to manage latch assessment, prenatal interventions to support lactogenesis and management of delayed lactogenesis. Participants placed relatively low importance on learning about latch assessment despite the central nature of this skill in supporting early breastfeeding.